Consider legal parameters, practical concerns of public debates, protests and demonstrations on campus. (March 2016) - Porter, Michael
Abstract : Many campuses have seen a significant uptick in vigorous verbal exchanges, protests and demonstrations, particularly related to race relations. This activity tests colleges' desire to create open dialogue while also fulfilling their obligations to provide a campus environment focused on learning and the safe exchange of ideas.